Nutritional analysis and acceptability of banana kepok flour and red bean flour cookies - Budiawan, Luqyana Hedi Nasywa; Nopriantini, Nopriantini; Rafiony, Ayu (ELECTRON (Journal of Science and Technology), 2025)
School children need nutritious food to fulfill their nutritional needs. Banana kepok flour and red bean flour can be utilized as raw materials for cookies as well as an alternative to wheat flour. Cookies from these two flours can be used as a snack for school children. This study aims to analyze nutrients and determine the acceptability of cookies made from kepok banana flour and red beans. The method used was experimental with three treatments: F1 (75%: 25%), F2 (50%: 50%), and F3 (25%: 75%). Organoleptic test was used to determine panelists' acceptance of color, aroma, taste, and texture. Nutrient analysis used proximate test to determine carbohydrate, protein, fat, ash content, and water content. Organoleptic results showed the highest percentage in F1 (75%: 25%) with 47.8% carbohydrate content, 9.34% protein, 29.2% fat, 1.37% fiber, 1.81% ash content, and 4.78% water content. Friedman test showed there was an effect on the acceptability of aroma, but not on color, taste, and texture. For further research, it is recommended to modify the shape of cookies to make them more attractive to school children.